Hakekat Filsafat Terhadap Steganografi Sebagai Seni Pengamanan Data Berdasarkan Teori Plato - Sulindawaty Sulindawaty; Muhammad Zarlis (Jurnal Mantik Penusa, 2018)
Philosophy is the mother of all knowledge. "Philosophy is the collection of all knowledge where God, nature and man are the subject of his inquiry", Descartes. Al-Farabi (d. 950 AD) of the greatest Muslim philosopher before Ibnu Sina, said philosophy is the science of the natural world and aims to investigate the true nature. (Ahmad syadali). The essence of philosophy on data security technology is clearly visible on Plato's theory. Where the number of crimes and attacks on the communication system, requires strict data security efforts. This is to prevent the occurrence of threat aspects on the communication system so that data is not accepted or taken by parties that should not be. In the field of computer security, steganography is one art to hide data through a medium (text, image and sound). Keywords: Philosophy, Data Security, Steganography.